Towards the total synthesis of a dolabellane diterpenoid, and studies in synthetic organic electrochemistry - Mason, J (2018)
Chapter one begins with an introduction on the dolabellane diterpenoid natural product family, followed by a summary of the most recent total and formal syntheses of dolabellane diterpenoids. Previous work carried out in the Burton group towards the target natural product (1.5), a member of the dolabellane family, will also be discussed. We then discuss our own work towards the natural product target 1.5. Significant progress towards the racemic natural product target has been achieved, and we have isolated the product 1.252 that derives from the key ring-closing metathesis reaction of 1.240. We have also achieved multi-gram syntheses of both enantiomers of an advanced intermediate in the natural product synthesis, and this work is detailed at the end of Chapter one. The synthesis of both enantiomers of the target natural product will be crucial in confirming the absolute configuration of the target natural product, 1.5. Chapter two is focused on the field of synthetic organic electrochemistry, and the work that we have done using this synthetic tool. Although we were ultimately unsuccessful in our stated aim of replacing the manganese(III) based oxidant in the radical cyclisation of substrates containing a dicarbonyl functional group, several observations were made which we expect will guide future research in this area.